2008
DOI: 10.1016/j.ijmm.2007.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Flagella allow uropathogenic Escherichia coli ascension into murine kidneys

Abstract: Uropathogenic Escherichia coli (UPEC) cause bladder and kidney infections in human and mice. UPEC initiate many kidney infections by ascending out of infected bladders, but how this occurs is not well understood. To determine if the flagella were responsible for the ascension of UPEC to the kidneys, a fliC mutation in strain NU149 was created. The fliC mutant spread poorly on soft agar plates, and 12 hours post-inoculation of murine urinary tracts, ascension into the murine kidneys was compromised in this muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 27 publications
(35 reference statements)
2
31
0
Order By: Relevance
“…Motility is a known fitness trait of uropathogenic E. coli strains in the urinary tract and is needed for ascension of the ureters to reach the kidneys (13,53,54). Recent studies indicate that YcgR can bind c-di-GMP and then interact with the flagellar motor.…”
Section: Resultsmentioning
confidence: 99%
“…Motility is a known fitness trait of uropathogenic E. coli strains in the urinary tract and is needed for ascension of the ureters to reach the kidneys (13,53,54). Recent studies indicate that YcgR can bind c-di-GMP and then interact with the flagellar motor.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, our data suggest that flagellum-mediated motility or a proposed architectural function (42) is dispensable for CAUTI persistence once bacteria have colonized the bladder urine. The role of flagella during CAUTI pathogenicity is more likely to be relevant during onset of infection when bacteria ascend through the urethra to reach the bladder or up the urethers into the kidneys (43).…”
Section: Discussionmentioning
confidence: 99%
“…Type 1 fimbriae, expressed on the surfaces of E. coli and most of the Enterobacteriaceae (11), have been shown to be critical for colonization of the bladder by UPEC (27), and accordingly, genes encoding these fimbriae are highly expressed in vivo (53). While type 1 fimbriae allow UPEC to bind mannose-containing glycoprotein receptors, such as uroplakin (46,61), and establish infection in the bladder, our laboratory (33) and another (51) have recently shown that flagella allow UPEC to ascend from the bladder to the kidneys. Furthermore, flagellum production contributes to the fitness of UPEC during murine urinary tract colonization (34,60).…”
mentioning
confidence: 95%